The Level Of Parents Anxiety Towards Female Students Participating In Pencak Silat Martial Arts Training At Margasari Branch, Margasari Sub District, Tegal Regency - Muhammad Ardi Pratama; Donny Wira Yudha Kusuma; Adi S; Dwi Tiga Putri (Universitas Negeri Semarang, 2025)
This research to analyze the level of parental anxiety regarding female students participating in pencak silat martial arts training at Margasari Branch, Margasari Sub District, Tegal Regency. This research uses a quantitative approach with a descriptive design. Data collection technique used was purposive random sampling.The background of this research is the anxiety of parents whose daughters participate in pencak silat martial arts training. The problem of this research is that is not yet known whether there are differences between the anxiety levels of parents whose children participate in pencak silat martial arts training at Margasari Branch, Margasari Sub District, Tegal Regency. The sample of this study consisted of 35 respondents who were parents of students, comprising 18 parents of female students and 17 parents of male students. The parental anxiety variable was analyzed based on four main factors that is, motoric, cognitive, affective, and somatic. The results showed that of the 18 parents of female students, 11 respondents fell into the high anxiety category, 5 respondents into the moderate category, 3 respondents into the low category, and 0 respondents into the panic category. Meanwhile, among the 17 parents of male students, 4 respondents fell into the high anxiety category, 5 respondents into the moderate category, 8 respondents into the low category, and 0 respondents into the panic category Based on the research findings, it can be conclude that the anxiety levels of parents of female students are higher than those of parents of male students. A significant difference was found between the anxiety levels of parents of female and male students, based on the independent sample t-test (t = 2,536; p = 0,016). The average anxiety level for parents of female students was 49,5, while for parents of male students, it was 39,29. This study recommends further socialization to parents regarding the benefits and safety of pencak silat martial arts training, especially for female, to reduce anxiety levels and enhance their participation.